Proceso de atención de enfermería en paciente de 24 años de edad en estado de gestación de 39 semanas con pre-eclampsia. - Valencia Camacho, Jessica Edilma (2020)
Preeclampsia one of the hypertensive disorders attributed to pregnancy usually occur after the 20th week of gestation and may be present until childbirth and postpartum, scientific studies associate it with fetal maternal morbidity and mortality, is characterized by an increase in blood pressure ≥140/90 plus the presence of proteins in the urine (proteinuria), Preeclampsia ranges from 5% to 10% in developed countries, but this figure could rise to 18% in some developing countries, these disorders require specialized care in more complex units because their complications affect other systems and organs more often in the liver and kidneys. Prenatal monitoring, timely diagnosis, proper management, and childbirth are the most effective measures to reduce the mortality rate from this cause, lack of access to quality health care is the main obstacle to reducing maternal mortality, due to the location, because of the place, distance and lack of transportation to specialty hospitals. In some parts of the world, 50% of rural women live more than 5 km from the nearest hospital, according to the clinical practice guidelines of the Ministry of Public Health hypertensive disorders in pregnancy is considered as an gynecological emergency and protocols of action have been established at all levels of health care.